2008
DOI: 10.1128/jcm.00552-08
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Kinase Sequence Analysis of Herpes Simplex Virus Type 1 Strains Present in Different Compartments in an Atypical Impetiginous Rash on the Lesional Skin of a Burn Patient

Abstract: We report the case of a 23-year-old male burn patient with an unusual herpes simplex virus (HSV) skin manifestation. The clinical symptoms and results of HSV type 1 (HSV-1) UL23 polymorphism analysis from saliva and lesional skin underscores the need for performing molecular analysis of HSV-1 infections in burned patients presenting unusual skin lesions. CASE REPORTAn otherwise healthy, 23-year-old male patient with 32% total body surface area burns was transferred to our burn center. The patient sustained sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, no benefits of the acyclovir treatment could be seen. In most case reports and case series, authors suggest intravenous acyclovir therapy for clinically manifested HSV infections in burns [19,4248]. Matthews et al [26] discussed a prophylactic therapy with idoxuridine for acute HSV infections, however, this therapy was not used in their study.…”
Section: Discussionmentioning
confidence: 99%
“…However, no benefits of the acyclovir treatment could be seen. In most case reports and case series, authors suggest intravenous acyclovir therapy for clinically manifested HSV infections in burns [19,4248]. Matthews et al [26] discussed a prophylactic therapy with idoxuridine for acute HSV infections, however, this therapy was not used in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical isolates of HSV‐1 were obtained by microculture using human foreskin fibroblasts and Vero‐cell microculture. Specific cytopathic effects (CPE) were confirmed by anti‐HSV‐1/2‐gD‐immunoperoxidase staining as reported earlier 9 . In order to analyse potential HSV‐1 genotype variations of viral DNA from throat swabs, plasma and whole EDTA blood, we sequenced the viral UL23 and UL30 genes as described previously 9,10 .…”
Section: Methodsmentioning
confidence: 99%
“…Specific cytopathic effects (CPE) were confirmed by anti-HSV-1/2-gD-immunoperoxidase staining as reported earlier. 9 In order to analyse potential HSV-1 genotype variations of viral DNA from throat swabs, plasma and whole EDTA blood, we sequenced the viral UL23 and UL30 genes as described previously. 9,10 The relative frequency of distinct patterns of HSV-1 UL23/ UL30 polymorphisms from critically ill and surgical ICU patients were derived from the medical thesis of Emrich H (2013), those from SCT recipients from the medical thesis of Moritz (now Lohrengel) K. (2013) (Supplementary Methods, Tables S1-S4).…”
Section: Virological Methodsmentioning
confidence: 99%
“…Because of the rapid state of unconsciousness, PCR tests were performed to investigate the potential cause of infection and the results showed HSV-1-related encephalitis, probably due to viral reactivation [ 49 ]. However, milder symptoms such as a rash, vesicles, or vesicopustules might be quite easily misdiagnosed and treated as impetiginous, eventually leading to much more severe complications of the HSV infection [ 50 ]. In 1996, Byers et al demonstrated that 50% of burn patients showed the presence of HSV in the lung tissue and 16 patients developed acute respiratory distress syndrome (ARDS), among which 13 were infected by HSV [ 51 ].…”
Section: Herpesvirusesmentioning
confidence: 99%